Evaluating the Rising Incidence of Multidrug-Resistant and Extensively Drug-Resistant Salmonella typhi and Salmonella paratyphi in Sialkot City : Drug-Resistant Salmonella typhi in Sialkot - Zaman, Umair; Nasir, Shua; Asim, Shazia; Azmat, Junaid; Khan, Rana Muhammad Asad; Soomro, Abdul Karim (Pakistan Journal of Health Sciences, 2025)
In the Developing countries, Typhoid is one of the major health concerns. Most importantly the disease management is getting complicated due to multi and extensive drug resistance incidence. Objective: To investigate the incidence of causative agent’s salmonella typhi and para-typhi in the affected patients of Sialkot who were either multi drug resistant or extensive drug resistant. Methods: This descriptive cross-sectional study was conducted at the department of microbiology, Khawaja Muhammad Safdar medical college, Sialkot from January, 2024 to July, 2024. A total of 2000 patients with febrile illness were examined for the study, 500 samples of neonates were excluded and blood samples of remaining 1500 patients were collected. The blood samples were cultured on MacConkey agar and blood agar. Among the 1500 patients, only 73 were found to be infected with either Salmonella typhi or Salmonella paratyphi according to CLSI criteria. Antibiotic sensitivity was investigated and resistant to trimethoprim-sulfamethoxazole (septran), chloramphenicol, and ampicillin were labeled as multi drug resistant while resistant to ciprofloxacin and third generation cephalosporins in addition to aforementioned antibiotics were labeled as extensively drug resistant. Results: From a total of 1500 samples, n=73 salmonella positive samples were included in this research. Incidence of extensively drug resistant Salmonella was 23(32%) and multidrug drug resistant Salmonella was 7 (10%). Conclusion: This study highlighted significant resistance rates, emphasizing the need for sensible antibiotic prescriptions and judicious antimicrobial use to combat rising multidrug and extensive resistance.